The Degree of Leadership Styles Practiced by the Teaching Staff at the University College of Educational Sciences in Palestine and its Relation to the Mental Health of Students from their Points of View - Marshood, Jamal Mohammad; Marbou, Sahar Said (Journal of Educational and Psychological Sciences, 2022)
This study aimed at finding the degree of leadership styles practiced by the teaching staff at the University College of Educational Sciences in Palestine and its relation to the mental health of students from their points of view. In order to achieve the study objectives, the researchers followed the correlative descriptive approach, A two-axis questionnaire was developed, the first one was to measure leadership styles which consisted of (30) items distributed among three fields, and the second one was to measure the mental health level, which consisted of (30) items distributed among four fields. the sample of the study consisted of (144) students, who were chosen randomly in the academic year (2020-2021). The results of the study showed the degree of practiced leadership styles got a total average of (2.97 out of 5), which meant it had a moderate degree. Meanwhile, at the fields level, the democratic field got the highest average (3.47) with a (high) degree, then the autocratic got an average of (2.86) with a (medium) degree and finally the terrestrial field got an average of (2.60) a (low) degree. The results also showed the mental health got a total average of (3.78 out of 5), which meant it had a (high) level. On the other hand, at the fields level, self-realization got the highest average with (3.90), physical health with an average of (3.79), social adjustment with an average of (3.72), and finally emotional balance with an average of (3.69). All of which were at a (high) level. In addition to this there was a positive correlation between the practiced leadership styles degree and the mental health degree level. In the light of the study results the researchers presented a set of recommendations and suggestions.